Pengaruh Strategi Dakwah Implementor Ecomasjid Terhadap Kesadaran Masyarakat Menghadapi Perubahan Iklim - darto, Darto; Saefullah, Chatib; Rahman, Encep Taufik (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to reveal the distribution of EcoMasjid implementors’ da’wah strategies, the level of public awareness of climate change, and the impact of these strategies on public awareness of climate change. This research uses a quantitative approach with a simple linear regression method. The theories used in this study include Behaviorism Theory, Stimulus-Organism-Response, Bayanuni Da’wah Strategy, and Festinger’s Cognitive Dissonance. The results show: (1) the distribution of da’wah strategies is 58.2% al-Athifi, 27.6% al-Aqli, and 14.3% al-Hissi; (2) 76.5% of respondents consider climate change important, 17.3% do not, and 6.1% are unsure; (3) Da’wah strategies are directly proportional to the increase in public awareness, with a positive relationship between the variables. The calculated t-value is 28.318, greater than the table value of 1.985, and the effect size is 89.3%, leading to the conclusion that H0 is rejected and H1 is accepted